2016
DOI: 10.1186/s41100-016-0041-3
|View full text |Cite
|
Sign up to set email alerts
|

Kocuria kristinae septic arthritis associated with infectious endocarditis in a hemodialysis patient with diabetes mellitus: a case report and literature review

Abstract: Background: Kocuria kristinae is an aerobic Gram-positive coccus that is considered ubiquitous and nonpathogenic in healthy individuals. Furthermore, only 27 reports have described cases of critical infections with this microorganism, which is notoriously difficult to identify. Case presentation: We report the case of a 61-year-old male hemodialysis patient with diabetes mellitus, who developed severe septic arthritis that was associated with infectious endocarditis, which was identified using 18 F-fluorodeoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…Out of 4399 samples, 30 (1.33%) isolates of Kocuria spp., the percentage of Kocuria spp. in female 20(0.76%) was higher than those in male patients 10(0.57%), our result not agree to results recorded by Horino et al [23] reported cases 38 of K.kristinae infections 12 female and 16 male hemodialysis patient with diabetes mellitus, while Pauli et al reported that the apparently healthy woman of acute 3940 bacterial meningitis due to Kocuria rosea with fulminant course and fatal outcome. The differences of number of Kocuria spp.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Out of 4399 samples, 30 (1.33%) isolates of Kocuria spp., the percentage of Kocuria spp. in female 20(0.76%) was higher than those in male patients 10(0.57%), our result not agree to results recorded by Horino et al [23] reported cases 38 of K.kristinae infections 12 female and 16 male hemodialysis patient with diabetes mellitus, while Pauli et al reported that the apparently healthy woman of acute 3940 bacterial meningitis due to Kocuria rosea with fulminant course and fatal outcome. The differences of number of Kocuria spp.…”
Section: Discussioncontrasting
confidence: 84%
“…"By routine conventional tests, it can easily be mistaken for Micrococcus and coagulase negative Staphylococci cultures is more of a challenge and requires detailed clinical history before labeling the organism as contaminant or commensal. The newer diagnostic methods such as Vitek 2 and 16S RNA based genotypic assay are more accurate in identifying this organism and thus help preventing its erroneous identification" [23].…”
Section: Discussionmentioning
confidence: 99%
“…After the exclusion of the duplicate articles, the record screening, and the snowball procedure, only 73 studies met the inclusion criteria. These 73 studies provided data on 102 patients, and these data were included in the analysis [ 4 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ,…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the identification of the studied bacteria in locations other than blood, seven cases with true infection were found, including septic arthritis caused by R. mucilaginosa and arthritis, peritonitis, and pacemaker infection caused by Kocuria spp. Except for Kocuria peritonitis, these infections have previously been identified although only published in a few case reports, with each making these findings among the first published ( 30 34 ). The adjustments for pediatric blood cultures and for infections outside the bloodstream are somewhat less robust than the ones used for adults with bloodstream infection.…”
Section: Discussionmentioning
confidence: 99%